2007
DOI: 10.1071/fp06306
|View full text |Cite
|
Sign up to set email alerts
|

A model of daily mean canopy conductance for calculating transpiration of olive canopies

Abstract: We tested the hypothesis that the transpiration (λEp) of high-coupled canopies, such as olive groves, may be calculated on a daily basis with sufficient precision by the Penman–Monteith ‘big leaf’ equation, by a model of bulk daily canopy conductance (gc) capable of scaling for canopy dimension. Given the limited data required, such a model could replace the standard approach (ET0 × Kc) for calculating olive water requirements, enhancing the precision of estimates. We developed a specific model of daily gc for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 38 publications
4
20
0
1
Order By: Relevance
“…The same observations have been reported during the calibration stage (see the previous section). Indeed, the AquaCrop adopts the FAO-56 dual approach (Allen et al, 1998) for calculating ET cact and this approach has generated much criticism when applied in the semi-arid Mediterranean region (e.g., Testi et al, 2004;Katerji and Rana, 2006;Lovelli et al, 2007;Orgaz et al, 2007;Er-Raki et al, 2007, 2009, 2010c as reported by Katerji et al (2013).…”
Section: Validation Of the Aquacrop Modelmentioning
confidence: 98%
“…The same observations have been reported during the calibration stage (see the previous section). Indeed, the AquaCrop adopts the FAO-56 dual approach (Allen et al, 1998) for calculating ET cact and this approach has generated much criticism when applied in the semi-arid Mediterranean region (e.g., Testi et al, 2004;Katerji and Rana, 2006;Lovelli et al, 2007;Orgaz et al, 2007;Er-Raki et al, 2007, 2009, 2010c as reported by Katerji et al (2013).…”
Section: Validation Of the Aquacrop Modelmentioning
confidence: 98%
“…The amount of PAR intercepted by the canopy of olive tree was estimated by the model of PAR interception, initially developed by Mariscal et al (2000c) and later modified by Orgaz et al (2007).…”
Section: Plant Water Relationsmentioning
confidence: 99%
“…With data from year 2011, we calibrated the Orgaz gc equation (Orgaz et al, 2007) to our olive orchard conditions, to obtain the following gc equation (mm s -1 ) for our olive orchard:…”
Section: Tool Descriptionmentioning
confidence: 99%
“…Transpiration of olive trees is mainly controlled by canopy conductance, as derived with the model of Orgaz et al (2007). Nevertheless, the main challenge in such models remains the integration of the effect of water stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation